Denture wearing and mortality risk in edentulous American adults: A propensity score analysis. (September 2020) - Sabbah, Wael; Slade, Gary D.; Sanders, Anne E.; Bernabé, Eduardo
Abstract: Objective: To evaluate the association between complete denture use and subsequent mortality among edentulous adults. Methods: Data from 1649 edentulous adults who participated in the Third National Health and Nutritional Examination Survey were linked to public-use mortality files for the period up to December 2015. Denture wearing, defined as use of complete dentures in both arches (clinically inspected) all the time or only when awake, was compared to non-wearing, defined as use of dentures occasionally or not at all. The primary outcome was all-cause mortality. Data on 27 covariates, classified as sociodemographic characteristics, behavioral factors, health insurance, laboratory tests and general health status, were used to create propensity scores for weighted and matched analyses. Results: In weighted data, the difference in mortality rate between denture and non-denture wearers was 11.1 (95 %CI: 3.6–18.6) deaths per 1000 person-years and the number needed to treat (NNT) at 10 years was 12. Denture wearers had 15 % lower risk of death (HR: 0.85; 95 % CI: 0.73−0.98) than non-denture wearers. In the matched sample, the mortality rate difference between denture and non-denture wearers was 8.8 (95 %CI: 0.2–17.4) deaths per 1000 person-years and the NNT at 10 years was 11. Risk of death was 21 % lower among denture wearers (HR: 0.79; 95 % CI: 0.68, 0.92) than non-denture wearers. Conclusion: This longitudinal analysis showed that the use of complete dentures was associated with longer survival and lower all-cause mortality risk among American edentulous adults. NNT is interpreted as one death prevented after 10 years for every twelve rehabilitated dentitions with removable complete dentures. Clinical Significance: Edentulous adults wearing complete dentures had longer survival and lower overall mortality risk than non-denture wearers, suggesting that prosthodontic rehabilitation with removable complete dentures might have benefits beyond restoring oral functioning.